Sea surface topography retrieved from GNSS reflectometry phase data of the GEOHALO flight mission. Issue 3 (11th February 2014) - Semmling, A. M.; Beckheinrich, J.; Wickert, J.; Beyerle, G.; Schön, S.; Fabra, F.; Pflug, H.; He, K.; Schwabe, J.; Scheinert, M.
Abstract Sea surface topography observations are deduced from an airborne reflectometry experiment. A GNSS (Global Navigation Satellite System) receiver dedicated for reflectometry was set up aboard the German HALO (High Altitude Long Range) research aircraft. Flights were conducted over the Mediterranean Sea about 3500 m above sea level. A signal path model divided into large‐ and small‐scale contributions is used for phase altimetry. The results depict geoid undulations and resolve anomalies of the sea surface topography. For the whole experiment 65 tracks over the Mediterranean Sea are retrieved and compared with a topography model. Tracks differ between right‐handed and left‐handed circular polarization. The difference, however, is not significant for this study. Precision and spatial resolution decrease disproportionately at low elevations. Eight tracks with centimeter precision are obtained between 11° and 33° of elevation. At higher elevation angles the number of tracks is significantly reduced due to surface roughness. In future such retrievals could contribute to ocean eddy detection.